The impact of diet on the inflammatory bowel disease course – a literature review - Nowotarska, Agnieszka; Błaszczyński, Gustaw; Nojek, Paweł; Pawlik, Wiktoria; Zimonczyk, Mariusz; Zawół, Monika; Jaglarz, Karolina; Kuca, Maciej (Journal of Education, Health and Sport, 2024)
Introduction and Objective. Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), is a chronic gastrointestinal disorder marked by relapsing symptoms. Current treatments mainly involve immunosuppressive therapies, which are effective but may have significant side effects. Diet as an adjunctive treatment is appealing due to its accessibility, low cost, and minimal adverse effects. This review explores the role of diet in managing IBD, focusing on dietary strategies during both active disease and remission. Methods. A literature review was conducted using PubMed and Google Scholar with search terms like "inflammatory bowel disease", "Crohn’s disease", "ulcerative colitis", "diet", "IBD treatment", "anti-inflammatory food" and related variations. Articles published within the last five years were prioritized. Brief description of the state of Knowledge. Ulcerative colitis and Crohn’s disease cause gastrointestinal inflammation. Crohn’s disease symptoms include abdominal pain, fistulas and rectal lesions, while UC is characterized by diarrhea, severe discomfort, and blood in the stool. Certain foods often exacerbate IBD symptoms. Proper nutrition during disease stages can improve patients’ quality of life. Diets high in processed foods, sugar, and red meat may increase IBD risk, while fiber and vitamin D3 are associated with fewer flare-ups. Regular malnutrition screening is essential for all IBD patients. Conclusions. Understanding the dietary components that influence inflammation in IBD could lead to better treatment outcomes and longer-lasting symptom relief. Integrating nutrition into personalized treatment strategies should become standard practice for managing IBD.